Securities dispute resolution in China - Zhu, Sanzhu (Ashgate Pub. Co., 2007)
During an era of growing foreign investment in China's securities market, this comprehensive and detailed study identifies the nature and types of securities disputes in China and the various procedures, including alternative dispute resolution, used to address them.